Efektivitas Instagram sebagai Media Komunikasi Pemasaran Agrowisata Kumulilir di Desa Sebatu, Kecamatan Tegalalang, Kabupaten Gianyar - SASTIARI, GUSTI AYU NINDIA; PITANA, I GDE; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
The Effectiveness Of Instagram As a Communication Media for Kumulilir Agrotourism Marketing in Sebatu Village, Tegalalang District, Gianyar Regency.  Marketing communication is an effort to make all marketing and promotional activities of the company to create an image or image that is one and consistent for consumers, so that consumers can get to know products/services, become interested and make purchases. The results of the study show several things. First, the characteristics who accessing the Instagram account @kumulilir are mostly women with an age range of 17-26 years with a Diploma/Bachelor level of education. Second, Instagram @kumulilir as a visual marketing communication medium is in the Attractive category. Third, analysis of Instagram @kumulilir as a marketing communication showed effective results through the measurement of the AIDA concept. This shows that the use of Instagram as a marketing communication medium is effective in introducing a business, providing explanations and being able to influence and attract consumers to visit through the content uploaded on the Agrowisata Kumulilir Instagram account. Kumulilir Agrotourism is suggested to be more intense in uploading content that contains information related to activities and matters related to Kumulilir Agrotourism so as to create tourist interest to visit.